2009
DOI: 10.1038/modpathol.2009.110
|View full text |Cite
|
Sign up to set email alerts
|

Calretinin immunohistochemistry: a simple and efficient tool to diagnose Hirschsprung disease

Abstract: Diagnosis of Hirschsprung disease (HD) is quite entirely based on the histopathological analysis of suction rectal biopsies. This hematoxylin and eosin approach has some limitations, despite the help of acetylcholinesterase staining. The aim of this study was to assess the diagnostic value of calretinin immunochemistry as a simple and reliable method in the diagnosis of HD. A total of 131 initial rectal biopsies carried out for suspicion of HD in children were retrieved, and calretinin immunohistochemistry was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
102
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 22 publications
11
102
2
Order By: Relevance
“…6 Absence of calretinin expression was first reported in patients with HD in 2004 6 in resection specimens. Two follow-up studies 7,8 confirmed these findings in RSBs. Holland et al 9 in 2011 described a sensitivity of 100% and a specificity of 83% when classifying HD status based on calretinin stain results.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…6 Absence of calretinin expression was first reported in patients with HD in 2004 6 in resection specimens. Two follow-up studies 7,8 confirmed these findings in RSBs. Holland et al 9 in 2011 described a sensitivity of 100% and a specificity of 83% when classifying HD status based on calretinin stain results.…”
supporting
confidence: 73%
“…In addition, AChE activity fades after time, requiring continual replenishment of HD control tissue. Moreover, interpreting AChE patterns requires experience, and AChE staining has been associated with relatively high rates of interobserver disagreement 7,8 as well as false-positive results.…”
Section: According To a Recent Consensus Article By The Gastro 2009mentioning
confidence: 99%
“…There were fewer major discrepancies and fewer equivocal interpretations. In addition, Guinard-Samuel et al 26 immunostained 131 cases of suspected Hirschsprung disease with calretinin, and also concluded that this immunohistochemical stain was superior to acetylcholinesterase in this clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…14 According to Gonzalo DH, all 12 of the patients without the Hirschsprung disease had Calretininpositive nerve fibers in lamina propria or the muscularis mucosae, and all 5 of patients with Hirschsprung disease had no staining of the nerves i.e. Calretinin-negative.…”
Section: Discussionmentioning
confidence: 99%